Fluorescence in robotic surgery. Issue 3 (13th May 2015) - Daskalaki, Despoina; Aguilera, Fabiola; Patton, Kristin; Giulianotti, Pier Cristoforo; Berber, Eren
<x xml:space="preserve">Abstract</x> Currently, there are several clinical applications for intraoperative ICG, such as identification of vascular and biliary anatomy, assessment of organ and tissue perfusion, lymph node mapping, and real‐time identification of lesions. In this paper we present a review of the available literature related to the use of ICG fluorescence in robotic surgery in order to provide a better understanding of the current applications, show the rapid growth of this technique, and demonstrate the potential future applications. J. Surg. Oncol. 2015; 112:250–256. © 2015 Wiley Periodicals, Inc.